(untitled) (CIPEEX, 2025)
This work investigates the concrete impacts of ADPF 347 on the penitentiary system of the State of Goiás, evaluating whether the structural decision of the Supreme Federal Court effectively improved prison conditions. The objective is to analyze how the measures imposed by the Court translated into local reforms, assessing both their advances and limitations. The methodology includes the examination of official sources, such as the 2009 Parliamentary Inquiry Commission on Incarceration and the 2023 inspection reports of the National Justice Council, alongside the analysis of post-ADPF 347 initiatives like custody hearings and the “Respect Modules.” The results reveal that Goiás implemented innovative programs aimed at reducing overcrowding and fostering more humane coexistence among inmates, producing partial improvements in the penitentiary environment. However, the persistence of overcrowding, recurrent violence, and insufficient financial and human resources demonstrates that the reforms are still fragile and uneven. The conclusion affirms that while ADPF 347 stimulated a shift in prison management and promoted relevant progress in Goiás, the effectiveness of these structural measures remains limited, requiring continuous monitoring by the judiciary, greater coordination with the executive and legislative branches, and sustained investment to guarantee the full protection of human rights within the prison system.